2007
DOI: 10.2135/cropsci2005.11.0432
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Regulators Alter Kentucky Bluegrass Canopy Leaf Area and Carbon Exchange

Abstract: Turf managers apply plant growth regulators (PGRs) throughout the growing season to reduce clipping production, provide a uniform canopy, and increase color. Reduced efficacy of trinexapac‐ethyl (TE) [4‐(cyclopropyl‐α‐hydroxy‐methylene)‐3,5‐dioxocyclohexanecarboxylic acid ethyl ester] and paclobutrazol (PAC) [(2RS, 3RS)‐1‐(4‐chlorophenyl)‐4,4‐dimethyl‐2‐(1H‐1,2,4‐triazol‐1‐yl) pentan‐3‐ol] has been reported during warmer summer months. Plant growth regulator dissipation and Kentucky bluegrass (KBG; Poa pratens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 27 publications
1
21
3
Order By: Relevance
“…The results of this study in conjunction with previously conducted experiments examining PGR effects on turf CERs fail to provide a clear cause‐and‐effect relationship between PGR altered CERs and reduced clipping production (Beasley and Branham, 2007; Gaussoin et al, 1997; Spokas and Cooper, 1991). Patterns of CER alteration from PGR applications appear to fluctuate greatly for gibberellin inhibitors.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The results of this study in conjunction with previously conducted experiments examining PGR effects on turf CERs fail to provide a clear cause‐and‐effect relationship between PGR altered CERs and reduced clipping production (Beasley and Branham, 2007; Gaussoin et al, 1997; Spokas and Cooper, 1991). Patterns of CER alteration from PGR applications appear to fluctuate greatly for gibberellin inhibitors.…”
Section: Discussioncontrasting
confidence: 69%
“…Patterns of CER alteration from PGR applications appear to fluctuate greatly for gibberellin inhibitors. The effects of PGRs on CERs are the result of, or a combination of, leaf and tiller production, changes in leaf morphology, increased chlorophyll density, and changes in sink demand for photoassimilates (Beasley and Branham, 2007; Gaussoin et al, 1997; Spokas and Cooper, 1991). Since TE and PAC are metabolized quickly within plant tissues, fluctuations in single‐leaf CERs from TE and PAC applications may be in response to changes in plant photoassimilate demand and growth patterns and not the cause of altered growth.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature has been reported to affect TE efficacy on hybrid bermudagrass and Kentucky bluegrass ( Poa pratensis L.) (Lickfeldt et al, 2001; Fagerness et al, 2002; Beasley and Branham, 2007; Beasley et al, 2007). Fagerness et al (2002) showed that TE provided greater growth suppression duration and magnitude of ‘Tifway’ bermudagrass at 20/10°C day/night air temperatures as opposed to 35/25°C.…”
mentioning
confidence: 99%
“…The previous two studies explored TE efficacy at different air temperatures controlled within growth chamber experiments. Beasley et al (2007) and Lickfeldt et al (2001) showed TE applications were more effective on Kentucky bluegrass (i.e., greater magnitude and duration of growth suppression) during cooler air temperatures of the spring and fall compared with applications during summer months.…”
mentioning
confidence: 99%
“…Such measures can be divided into three main categories: (i) the selection and breeding of genotypes with improved drought tolerance; (ii) an increase in the soil retention capacity and reduction of evaporation from soil surface, and (iii) cultivation measures improving the efficient use of water by plants, which include, for example, the use of growth regulators. In general, the growth regulators can contribute to improving effective use of water in particular by increasing the rooting depth or root water extraction from soil (Marcum and Jiang 1997), increasing the root:shoot ratio (Rajala and Peltonen-Sainio 2001), reducing leaf area (Beasley et al 2007) and accumulation of osmoregulatory substances (Akram et al 2012), increasing the accumulation of antioxidants (Wu and von Tiedemann 2001), supporting stomatal regulation (Bingham and McCabe 2006), reducing rate of leaf senescence (Cromey et al 2004) etc. However, very often contradictory effects of plant regulators on plant physiology and yield formation under water deficit are reported (e.g.…”
mentioning
confidence: 99%